What Industrial Categories Are Workers at Excess Risk of Filing a COVID-19 Workers' Compensation Claim? A Study Conducted in 11 Midwestern US States. Issue 5 (May 2021) - Bernacki, Edward J.; Hunt, Dan L.; Yuspeh, Larry; Lavin, Robert A.; Kalia, Nimisha; Leung, Nina; Tsourmas, Nicholas F.; Williams, Leila; Tao, Xuguang (Grant)
Abstract : Objective: Determine the industries with the highest proportion of accepted COVID-19 related workers' compensation (WC) claims. Methods: Study included 21, 336 WC claims (1898 COVID-19 and 19, 438 other claims) that were filed between January 1, 2020 and August 31, 2020 from 11 states in the Midwest United States. Result: The overwhelming proportion of all COVID-19 related WC claims submitted and accepted were from healthcare workers (83.77%). Healthcare was the only industrial classification that was at significantly higher COVID-19 WC claim submission risk (odds ratio [OR]: 4.00; 95% confidence intervals [CI]: 2.77 to 5.79) controlling for type of employment, sex, age, and presumption of COVID-19 work-relatedness. Within healthcare employment, WC claims submitted by workers in medical laboratories had the highest risk (crude rate ratio of 8.78). Conclusion: Healthcare employment is associated with an increased risk of developing COVID-19 infections and submitting a workers' compensation claim.